Investigation of nitrate pollution of the hydrosphere in the transboundary area of seversky donets river basin - Виставна, Юлія Юріївна; Яковлєв, Валерій Володимирович; Дядін, Дмитро Володимирович; Вергелес, Юрій Ігоревич; Чистикова, Анна Володимирівна; Жидких, Ірина Олегівна (Eastern-European Journal of Enterprise Technologies, 2014)
The aim of the research was to determine the distribution patterns of dissolved substances, in particular nitrates in surface and ground water. Water sampling was carried out on the Udy, Lopan, Oskol and Seversky Donets rivers and groundwater on the left and right banks of rivers. The results have shown that water-rock interaction and evaporation are predominant natural factors that affect the macroelement composition of natural water. Nitrates had high spatial and temporal variations in surface and ground water. The average nitrate content in groundwater was 26.7 mg/l, and in river water - 6.9 mg/l. Annual nitrate removal from groundwater into rivers was 3 tons/km2. About 1/5 spring water samples were characterized by a higher nitrate content than the standards, recommended by the World Health Organization and national water quality standards.